Crystal structure and configuration revision of 9-hydroxy-7, 8-dehydro-sarcotrocheliol and sarcotrocheliol. Issue 20 (18th October 2019) - Hamed, Abdelaaty; Issa, Marwa Y.; Ghani, Mohamed A.; Frese, Marcel; Neumann, Beate; Stammler, Hans Georg; Sewald, Norbert; Shaaban, Mohamed
Abstract: Herein, we report the isolation and stereo-structure of rare pyrane-based cembranoid diterpenes, 9-hydroxy-7, 8-dehydro-sarcotrocheliol (1 ) and sarcotrocheliol (2 ), from Sarcophyton trocheliophorum collected from Red Sea. Absolute configurations of both compounds were revised based on single crystal X-ray analyses. Graphical Abstract: